Combined Effect of Microneedling and Platelet-Rich Plasma for the Treatment of Acne Scars: A Meta-Analysis - Kang, Cheng; Lu, Dakai (Frontiers in Medicine, 2022)
Background: Microneedling is a promising method for the treatment of acne scars, while the effect of microneedling combined with platelet-rich plasma (PRP) remains unknown. We performed a meta-analysis of controlled studies to compare the efficacy and safety of microneedling treatment with and without additional PRP in patients with acne scars. Methods: Randomized and non-randomized controlled studies were identified by search of Medline, Embase, and Cochrane’s Library databases. Results were pooled with a random-effects model incorporating the possible heterogeneity. Results: Four randomized and ten split-face non-randomized controlled studies with 472 patients were included. Compared to microneedling therapy without PRP, combined treatment with microneedling and PRP was associated with increased odds of clinical improvement of > 50% in Goodman’s Qualitative scale (GQS: odds ratio [OR]: 2.97, 95% confidence interval [CI]: 1.96 to 4.51, P < 0.001; I2 = 0%), and a significantly improved mean GQS score (mean difference: -0.32, 95% CI: -0.44 to -0.20, P < 0.001; I2 = 0%). Combined treatment was associated with a higher patient satisfying rate (OR: 4.15, 95% CI: 2.13 to 8.09, P < 0.001; I2 = 53%), while the incidence of severe adverse events such as severe erythema (OR: 1.59, 95% CI： 0.73 to 3.46, P = 0.24; I2 = 0%) and severe edema (OR: 1.14, 95% CI： 0.47 to 2.76, P = 0.77; I2 = 0%) were not significantly different. Conclusions: Combined treatment with microneedling with PRP is more effective than microneedling without PRP for patients with acne scars.